(untitled) (Swiss Medical Weekly, 2023)
BACKGROUND AND AIM: Liver transplant recipients show suboptimal vaccine-elicited immune responses to severe acute respiratory coronavirus 2 (SARS-CoV-2) vaccination. This study aimed to assess real-world data on SARS-CoV-2 antibodies after the second and third SARS-CoV-2 vaccination in liver transplant recipients in Switzerland. METHODS: We enrolled liver transplant recipients who attended regular follow-up visits between 01/07/2021 and 30/04/2022 at the outpatient clinic of the Department of Visceral Surgery and Medicine at Bern University Hospital, Switzerland. Following the Swiss Federal Office of Public Health recommendations, we measured SARS-CoV-2 anti-spike IgG antibodies in 117 liver transplant recipients ≥4 weeks after the second SARS-CoV-2 mRNA vaccination from 07/2021–04/2022. In case of antibody levels of <100 AU/ml, patients received a third vaccination and antibodies were re-measured. Patients with antibody levels of >100 AU/ml were defined as “responders”, those with 12–100 AU/ml as “partial responders” and those with <12 AU/ml as “non-responders”. RESULTS: After two vaccinations, 36/117 (31%) were responders, 42/117 (36%) were partial responders and 39/117 (33%) were non-responders. The humoral immune response improved significantly after the third vaccination, resulting in 31/55 (56%) responders among the previous partial or non-responders. A total of 26 patients developed COVID-19, of whom two had a moderate or severe course (both non-responders after three doses). DISCUSSION: One third of liver transplant recipients showed an optimal response following two vaccinations; a third dose achieved a complete antibody response in more than half of partial and non-responders. We observed only one severe course of COVID-19 and no deaths from COVID-19 in the vaccinated liver transplant recipients.